Recent insights into metallic nanoparticles in shelf-life extension of agrifoods: Properties, green synthesis, and major applications - Kumar, Ankit; Kumar, Abhishek; Vats, Chaman; Sangwan, Pooja; Kumar, Vikash; Abhineet,; Chauhan, Prashant; Chauhan, Ravinder S.; Chaudhary, Kautilya (Frontiers in Sustainable Food Systems, 2022)
Nanotechnology emerged as a revolutionary technology in various fields of applied sciences i.e., biomedical, engineering, and food technology. The pivotal roles of nano compounds have been explored by various researchers i.e., in food protection, preservation, and enhancement of shelf life. In this sequence, metallic nanoparticles (MNPs) are proven to be useful in developing products with antimicrobial activity and subsequently improve the shelf life of agri-foods. The major application MNPs has been observed in the packaging industry due to the combining ability of biopolymers with these MNPs. In recent years, various metal nanoparticles have been explored to formulate various active food packaging materials. However, the method of production and need for risk evaluation is still a topic of discussion among researchers around the world. Generally, the MNPs are synthesized by various chemical and physical means which may pose variable health risks. To overcome such issues, the green synthesis of MNPs using microbial and plant extracts has been proposed by various researchers. In this review, we are aiming to explore the green synthesis of MNPs, their properties, characterization, various ways of utilizing them to extend the shelf life, and most important the risk associated with them along with their quality and safety considerations. Keywords: MNPs, Nanoparticles, Green Synthesis, Shelf-life, Agri-foods